Financial Literacy, Financial Attitudes, and the Environment on Investment Decisions Through Investment Intention - Al Qoriana, Viaulia; Ningtyas, Mega Noerman (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to explore the relationship between financial literacy, financial attitudes, and social, economic, and family environment towards investment decisions through investment intention among Generation Z investors in Malang City. The research methods used are quantitative approaches and associative methods. A sample of 400 Generation Z investors was selected using nonprobability sampling with a purposive sampling approach. Data were collected through an online questionnaire and analyzed using the Structural Equation Model (SEM) with a Partial Least Square (PLS) approach. The results showed that financial literacy and social, economic, and family environment have a significant influence on investment intention and investment decisions. However, financial attitudes only have a significant effect on intention in investing in the capital market, but not significantly in making investment decisions.